Perfil populacional e sanitário de cães e gatos associado ao perfil socioeconômico dos proprietários em áreas assistidas por estratégias de saúde da família - Felipetto, Laís Giuliani (2018)
Approximately 60% of Brazilian households have at least one pet, which represents 52 and 17 million dogs and cats domiciled, respectively. The increasing acquisition of these as pets, coupled to the fact that they are living with their tutors in homes and attending public areas, increases the number of people exposed to the risk of contracting zoonotic infections. Knowledge about the presence, numbers, and habits of animals, as well as the care given to them, are essential for the planning of prophylaxis strategies to prevent or minimize zoonotic infections. This study aimed to carry out a situational analysis of areas assisted by Family Health Strategies (FHS) in the municipality of Santa Maria, RS. The population and health profile of the dogs and cats of the residences was estimated, associated with the socioeconomic profile of the interviewee. The methodology used was the use of questionnaires, in a cross-sectional population-based study. To determine the number of residences participating in the survey, randomized stratified sampling was performed, according to the number of families that were registered in the Analytical Household Registration of each FHS. The results presented are the first described in the literature regarding pet animals in the FHS area in Brazil. 414 households were investigated, with 85.5% of the respondents reporting having pets, of which 55.6% had only dogs, 6% only cats and 38.4% dogs and cats. The average number of animals per residence was 3 (2.2 dog and 0.8 cat) and the number of inhabitants was 3.3; with the proportion of 1 man for each 0.9 animal, the proportion presented in the study was the largest already described in the national and international literature. There was no significant association between the amount of animals (dog and / or cat) and the family have in their composition children or elderly. The interviewee's schooling and family income were not associated with the amount of animals. However, they have been associated with sterilization, veterinary monitoring, vaccination, endoparasiticidal treatment and treatment for ectoparasites of dogs and cats. The results of this study show the need to adopt public health policies and education that guide the population about responsible ownership animal, the importance of population control, and the risks of zoonoses. In addition, the research reinforces the need to include the veterinarian in basic health care, through the Family Health Support Center (FHSC), in order to promote human and animal health in the context of single health.